Altered Brain Activation During Memory Retrieval Precedes and Predicts Conversion to Psychosis in Individuals at Clinical High Risk. (11th September 2018) - Cao, Hengyi; McEwen, Sarah C; Chung, Yoonho; Chén, Oliver Y; Bearden, Carrie E; Addington, Jean; Goodyear, Bradley; Cadenhead, Kristin S; Mirzakhanian, Heline; Cornblatt, Barbara A; Carrión, Ricardo E; Mathalon, Daniel H; et al.
Abstract: Memory deficits are a hallmark of psychotic disorders such as schizophrenia. However, whether the neural dysfunction underlying these deficits is present before the onset of illness and potentially predicts conversion to psychosis is unclear. In this study, we investigated brain functional alterations during memory processing in a sample of 155 individuals at clinical high risk (including 18 subjects who later converted to full psychosis) and 108 healthy controls drawn from the second phase of the North American Prodrome Longitudinal Study (NAPLS-2). All participants underwent functional magnetic resonance imaging with a paired-associate memory paradigm at the point of recruitment and were clinically followed up for approximately 2 years. We found that at baseline, subjects at high risk showed significantly higher activation during memory retrieval in the prefrontal, parietal, and bilateral temporal cortices ( P FWE < .035). This effect was more pronounced in converters than nonconverters and was particularly manifested in unmedicated subjects ( P < .001). The hyperactivation was significantly correlated with retrieval reaction time during scan in converters ( P = .009) but not in nonconverters and controls, suggesting an exaggerated retrieval effort. These findings suggest that hyperactivation during memory retrieval may mark processes associated with conversion to psychosis, and such measures have potential as biomarkers for psychosis prediction.